Climate-Smart Village in Olopa, Guatemala - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The Climate-Smart Village (TeSAC - Territorio Sostenible Adaptado al Clima in Spanish) is located in El Bendito village, municipality of Olopa in East side of Guatemala. The villagers are from the chortÃ ethnicity and cultivate coffee and basic grains (maize and beans) Photos: J.L.Urrea (CCAFS)